Need Analysis for The Development of Augmented Reality-Based Electronic Design Application in Secondary School Design and Technology (D&T) Subject - Zuhaili Mohd Arshad; Mohamed Nor Azhari; Riris Setyo Sundari (Journal of Advanced Research in Applied Sciences and Engineering Technology, 2023)
Students should be introduced to computer programming in order to generate computer programming experts. However, there are many constraints in introducing students to the basics of programming and microcontrollers in Design and Technology subjects in schools. The use of the latest technology is becoming a demand in implementing the best teaching and learning and it has been an essential component of the educational process. One of the latest technologies used in education is Augmented reality which has a positive effect on students’ learning. The study used a Design and Development Research (DDR) design consisting of three phases. This paper discusses the findings of the first phase (needs analysis) of the study, which was conducted to determine challenges in the implementation of the second form Design and Technology curriculum, the potential use of mobile devices in teaching and learning, as well as the need for the development of augmented reality-based Electronic Design learning applications as an aid in teaching in secondary school D&T subjects. Online surveys were employed in this study, and they were sent to second-form RBT teachers via school email. Statistical Packages for Social Science (SPSS) version 27.0 was used to perform a descriptive analysis of the study’s data using the mean (M) and standard deviation (SD). Based on the analysis of survey data among 138 respondents, it was discovered that the average mean value for the challenge aspect of T&L implementation for D&T subjects was at a moderate level (M = 2.68, SP =0.52), indicating that there is still much space for improvement in this aspect. Electronic Design is the topic that is the most challenging to implement into the second-form D&T curriculum. High levels of agreement were found in a descriptive examination of the teacher’s perceptions of the possible usage of mobile devices (M = 4.10, SD = 0.68). The average mean for the study of the development need of the augmented reality-based electronic design application is high (M = 3.89, SD = 0.55), indicating that it is necessary to develop it as a support material for second-form D&T courses. The findings of this study are crucial in ensuring that the design and development of a mobile application as a teaching aid for microcontroller education are put into practice and have a positive effect in enhancing secondary school students’ literacy in programming.